2006
DOI: 10.1038/sj.onc.1209762
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4 overexpression is a common characteristic of human carcinomas

Abstract: Tumor necrosis factor receptor (TNFR) associated factor 4 (TRAF4) was initially identified as a gene amplified and overexpressed in breast carcinomas. Our aim was to evaluate whether TRAF4 protein overexpression exists in other cancer types. Immunohistochemistry analysis of tumor samples from 623 patients with 20 different tumor types showed that TRAF4 was overexpressed in 268 tumors (43%), including 82 of 137 lung adenocarcinomas (60%). Interestingly, 32 primary tumors and their matching metastases exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 25 publications
5
85
0
1
Order By: Relevance
“…16 Interestingly, in mammary cancer cells, TRAF4 localization is altered: while it is still present in TJs in well differentiated tumors, the protein is relocalized in the cytoplasm and the nucleus in poorly differentiated tumors, indicating that TRAF4 functions differently in cancer cells. 8,9,16,20 TRAF4 is a typical TRAF protein composed of 3 distinct modular domains, an N-terminal RING domain, a succession of 7 zinc fingers (ZF), and a C-terminal TRAF domain. 15 The RING domain of TRAF4 was shown to confer an E3-ligase activity to the protein, the 7 central ZF have an unknown function but, by analogy with other TRAF proteins, are most probably involved in protein-protein interactions, and the TRAF domain governs the trimerization of the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Interestingly, in mammary cancer cells, TRAF4 localization is altered: while it is still present in TJs in well differentiated tumors, the protein is relocalized in the cytoplasm and the nucleus in poorly differentiated tumors, indicating that TRAF4 functions differently in cancer cells. 8,9,16,20 TRAF4 is a typical TRAF protein composed of 3 distinct modular domains, an N-terminal RING domain, a succession of 7 zinc fingers (ZF), and a C-terminal TRAF domain. 15 The RING domain of TRAF4 was shown to confer an E3-ligase activity to the protein, the 7 central ZF have an unknown function but, by analogy with other TRAF proteins, are most probably involved in protein-protein interactions, and the TRAF domain governs the trimerization of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11]12 TRAF4 belongs to the TRAF family which is composed of 7 members in human. 13,14 Unlike the other TRAF proteins, which function predominantly in inflammation and immunity, TRAF4 is mainly involved in developmental and morphogenetic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the previous study found some tumors to contain only nuclear TRAF4, although in that study most contained cytoplasmic staining and no link was made with differential localization and tumor differentiation. 25 These data imply that localization of TRAF4 is regulated differently in different tumors and that localization may influence differentiation processes of malignant squamous epithelial cells. The differential localization of TRAF4 and any consequent functional effects are tumor-specific events, since we did not observe cytoplasmic staining in normal tissue.…”
Section: Discussionmentioning
confidence: 92%
“…High level expression of TRAF4 was associated with amplification of the TRAF4 gene locus in a minority of the TRAF4-positive tumors, 25 implying that other regulatory factors lead to increased TRAF4 expression in some tumors. We found that TRAF4 is easily detectable using immunohistochemistry on primary human SCCHN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation